Blockchain-Based Access Control for Secure and Efficient Smart Homes in the Internet of Things (IoT) Era - Sangeeta Gupta, Mohammed Yasaruddin, M. Subramaniam (Mathematical Statistician and Engineering Applications, 2022)
This research paper explores the integration of blockchain technology with smart homes and the Internet of Things (IoT) to enhance security and access control. With the increasing proliferation of IoT devices in modern homes, ensuring secure and authorized access is crucial. Blockchain’s decentralized and immutable nature offers a promising solution for addressing security challenges. This project proposes a secure access control system that leverages the blockchain’s distributed ledger and cryptographic techniques. It facilitates user authentication, device authorization, and tamper-resistant audit trails. The study aims to enhance the overall security and privacy of smart homes while facilitating seamless interactions with IoT devices. By combining blockchain, smart home technology, and the IoT, this research contributes to the development of robust access control mechanisms for a connected and secure home environment.